Molecular Dynamics Simulation of the Cu/Au Nanoparticle Alloying Process. (31st October 2019) - Zhang, Linxing; Li, Qibin; Tian, Sen; Hong, Guang
Abstract : Sintering is an important approach for the alloying of different metals, which is affected by factors such as temperature, grain size, and material properties. And it represents a complex thermodynamic process. This paper had adopted the molecular dynamics methods to investigate the evolution process of nanostructure during the sintering of Cu and Au nanoparticles. The changes in crystalline during the nanosintering process were observed, and the radial distribution function of atoms, the shrinkage ratio, and the sintering neck of the systems were discussed. The initial sintering temperature and melting temperature of the system were obtained; at the same time, the characteristics of the sintering neck with changes in temperature during the nanosintering process were revealed.